Penggunaan Macam Pupuk dan Bentuk Aplikasinya Terhadap Pertumbuhan Bibit Kelapa Sawit di Pembibitan Utama - Nurseha Nurseha; Danner Sagala; Antonius Dalle (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2014)
The goal of this research was to know the effect of kinds and application methods of fertilizer on oil palm in main nursery.. The materials, used were Oil Palm Tenera Variety, Blitz Fertilizer and Mutiara Fertilizer. The experiment design was completely randomized design with 8 treatments in 5 replications. The treatment were fertilizer kinds and the application methods consisted of granular formed mutiara fertilizer, dissolved mutiara fertilizer, granular formed blitz fertilizer by 50% mutiara fertilizer dosage, dissolved blitz fertilizer by 50% mutiara fertilizer dosage, granular formed blitz fertilizer by 100% mutiara fertilizer dosage, dissolved blitz fertilizer by 100% mutiara fertilizer dosage, granular formed blitz fertilizer by 150% mutiara fertilizer dosage, dissolved blitz fertilizer by 150% mutiara fertilizer dosage. Mutiara fertilizer dosage were 10 grams/seedling for 5 month old, 15 grams/seedling for 6 month old and 15 grams/seedling for 7 month old. Measured variable were plant height, the girth of the stem and midrib number. The results showed that the use of blitz fertilizer by 100% mutiara fertilizer dosage with dissolved application gave the best growth in oil palm seedlings in the main nursery